SOFTWARE SIMULATION IN ARENA FOR SUGAR CANE INPUT - Rodrigues, Valéria Aparecida Roque; Herculani, Rhadler (Revista Interface Tecnológica, 2020)
This article deals with research in a sugar-alcohol plant that is evolving every year, seeking continuous improvement in its processes. This is noticed by the increase in its productivity and, in the current grinding, that is around 14,000 tons in 24 hours, you can have a loss of sixty thousand reais in one hour of stoppage. The objective of this work is to optimize the time of entry of sugar cane to the unloading table, avoiding losses with the stop of the process in the grinding. For this study, the method of timing was used to improve the time of entry of sugar cane into the unloading table, weighing time, analysis time and unloading table time. The ARENA simulation software is very and effective to carry out studies in the area of times and methods, in addition to demonstrating the entire download process in a simple way through a flowchart. Enabling decision making and reducing bottlenecks in the process, being of paramount importance for the improvement of all processes.